Hukum Islam dan Pengelolaan Keragaman Sosial: Resolusi Konflik Identitas dalam Perspektif Moderasi Beragama - Mega Mustika; Ridwan Malik; Siti Walida Mustamin (YUDHISTIRA : Jurnal Yurisprudensi, Hukum dan Peradilan, 2025)
The tension between the ideal of unity and the reality of social diversity in multicultural societies through the perspective of Islamic law. In the Indonesian context, such tension is not merely conceptual but is manifested in identity-based conflicts, divergent religious interpretations, interreligious relations, and the politicization of religion in the public sphere. Employing a normative-sociological approach with a library-based research design, this study analyzes classical and contemporary Islamic legal sources alongside relevant socio-religious phenomena. The article explores fundamental principles of Islamic law such as tawhid (oneness), ukhuwwah (brotherhood), ta‘aruf (mutual recognition), ikhtilaf (legitimate difference), and al-‘adl (justice) as normative foundations for managing diversity. The aim of this study is to explain the role of Islamic legal principles in managing social tensions in multicultural societies in order to achieve social harmony and integrity. The findings indicate that an Islamic legal approach grounded in maslahah (public interest), wasathiyah (moderation), and tasamuh (tolerance) has significant potential to reduce identity-based conflicts and promote social harmony. When interpreted contextually and moderately, Islamic law functions not only as a religious normative system but also as a social institution capable of safeguarding cohesion in plural societies. These findings underscore the importance of strengthening a moderate paradigm of Islamic law as both an ethical and juridical reference for managing social diversity in plural states.